Vertical Farming Innovation in Urban Netherlands: Sustainable Solutions with Modern Hydroponics - Nina, Nening; Lucas, Laura; Sridar, Katja (Yayasan Adra Karima Hubbi, 2024)
In the era of globalization and rapid population growth, agricultural land in urban areas is increasingly limited. As a country with a high population density, the Netherlands has adopted vertical farming innovations using modern hydroponics as an alternative to increasing the efficient use of space and resources. This research aims to evaluate the effectiveness of hydroponic vertical farming in urban areas in the Netherlands as a sustainable solution. Specifically, this research focuses on measuring the increase in productivity and reduction in environmental impact compared to traditional farming methods. This research uses a quantitative approach with an experimental design. Data were collected from several vertical farming locations in the urban Netherlands. Variables measured include plant productivity, water use, and carbon emissions. Data analysis was carried out using descriptive and inferential statistics. Results show that vertical farming with modern hydroponics in Dutch urban areas increases crop productivity by 40% and reduces water use by 60% compared to traditional agriculture. In addition, energy use is significantly reduced, which contributes to reduced carbon emissions. Vertical farming using modern hydroponic systems in Dutch urban areas offers an efficient, sustainable solution. By increasing productivity and reducing resource use, this technology could answer future agricultural challenges in dense urban areas. Further research is needed to optimize this technology and adapt it to various geographic and climatic conditions.